The relationship of the individual psychological characteristics of athletes with the effectiveness of competitive activity - Valentina Liashenko; Olga Kozhanova; Evgeny Korzh (Kharkiv State Academy of Physical Culture, 2020)
Purpose: to determine the relationship of individual psychological characteristics of athletes with the effectiveness of competitive activity. Material & Methods: to diagnose the level of self-esteem, we used the method of "Integral self-esteem of the personality", which allowed athletes to assess personal qualities and derive a general level of self-esteem. The methodology for determining the type of stress tolerance (N. P. Fetiskin, V. V. Kozlov, M. Manuylov) was used by us to determine the characteristic patterns of behavior in athletes in the event of a stressful situation [15]. To identify the severity of masculine and feminine characteristics in athletes, we used the questionnaire S. Boehm [14] a diagnostic technique for self-assessment of mental states developed by G. Aysenck [10] we used to determine such mental states as anxiety, frustration, aggressiveness and rigidity. To process the obtained results, methods of mathematical statistics were used. The study involved 50 athletes from a candidate for a masters of sports to a master of sports specializing in high-speed power athletics from 18 to 29 years old. Results: revealed the relationship of the individual psychological characteristics of athletes specializing in high-speed power athletics with the effectiveness of their competitive activities. Personal quality is neuroticism, has negative correlation with the best result of the season (r=-0.44) and the result in the main start (r=-0.39), and self-esteem has high positive relationships with the best result of the season (r=0.81) and the result at the main start (r=0.88). Conclusions: according to the results of our study, self-esteem has the greatest number of relationships with the studied indicators, including the readiness for competitive activity (r=0.80) and the result at the main start (r=0.88). We obtained a high degree of reliability of the differences between personality neurotization and competitive outcome. Thus, athletes who are confident in themselves, with adequate self-esteem, a low level of aggressiveness and anxiety, have high resistance to stressful conditions that arise in the process of competitive activity and can demonstrate high results.